Clinical differences between Mycoplasma pneumoniae pneumonia and Streptococcus pneumoniae pneumonia: a case control study - Jinping Ruan; Jinping Ruan; Zhou Fu; Linyan Ying; Linyan Ying; Linyan Ying (Frontiers in Pediatrics, 2024)
IntroductionMycoplasma pneumoniae pneumonia (MPP) and Streptococcus pneumoniae pneumonia (SPP) are frequent causes of respiratory tract infection, the aims of the study were to explore the differences in clinical features between children with MPP and those with SPP.MethodsThis retrospective study included admitted children who were diagnosed with MPP or SPP over 5 years from January 2015 to January 2020. Children with MPP were compared to children with SPP in terms of clinical features.Results506 patients with MPP were compared to 311 patients with SPP in terms of clinical differences. The MPP group with a median age of 60 [29–89] months and the SPP group with a median age of 24 [10–40] months. Patients with MPP were older and had a higher occurrence of receiving antibiotics before admission, fever, dry cough, polypnea and diarrhea than patients with SPP (all p < 0.01). Patients with SPP were more likely to have wheezing, cyanosis and irritability (all p < 0.01). Laboratory findings in our study showed that there were significant differences between MPP and SPP patients in mean leucocyte count, neutrophil % (N%), lymphocyte % (L%), ALT levels, AST levels, LDH levels and incidence of accelerated procalcitonin (PCT) (all p < 0.01). Lower age, no dry cough, no polypnea, lower LDH levels, and higher PCT might lead to the diagnosis of SPP. Our study showed that age had a higher accuracy in predicting MPP than LDH levels, with an age >48.5 months shown to be an independent predictive factor for the early evaluation and identification of MPP.DiscussionIn conclusion, patients with MPP and SPP usually present with fever, cough and some nonspecific symptoms. Our study showed that age, dry cough, polypnea, LDH levels, and PCT levels were independent predictive factors associated with MPP and SPP.